TECHNOLOGY, SCIENCE AND MORE - Lucena, Elkin (2015)
It is good that in times of more crude pragmatism, that is, when things are measured only by its results, regardless of the means used to achieve them, it's good, I repeat, we return to remind philosophers who will served as a reference to Western culture, to assume our responsibilities to society.